Systematic review and meta-analysis of the efficacy of prophylactic abdominal drainage in major liver resections - Abbasi Dezfouli, Sepehr; Ünal, Umut Kaan; Ghamarnejad, Omid; Khajeh, Elias; Ali-Hasan-Al-Saegh, Sadeq; Ramouz, Ali; Salehpour, Roozbeh; Golriz, Mohammad; Chang, De-Hua; Mieth, Markus; Hoffmann, Katrin; Probst, Pascal; et al. (Scientific reports, 2021)
Prophylactic drainage after major liver resection remains controversial. This systematic review and meta-analysis evaluate the value of prophylactic drainage after major liver resection. PubMed, Web of Science, and Cochrane Central were searched. Postoperative bile leak, bleeding, interventional drainage, wound infection, total complications, and length of hospital stay were the outcomes of interest. Dichotomous outcomes were presented as odds ratios (OR) and for continuous outcomes, weighted mean differences (MDs) were computed by the inverse variance method. Summary effect measures are presented together with their corresponding 95% confidence intervals (CI). The certainty of evidence was evaluated using the Grades of Research, Assessment, Development and Evaluation (GRADE) approach, which was mostly moderate for evaluated outcomes. Three randomized controlled trials and five non-randomized trials including 5,050 patients were included. Bile leakage rate was higher in the drain group (OR: 2.32; 95% CI 1.18-4.55; p = 0.01) and interventional drains were inserted more frequently in this group (OR: 1.53; 95% CI 1.11-2.10; p = 0.009). Total complications were higher (OR: 1.71; 95% CI 1.45-2.03; p < 0.001) and length of hospital stay was longer (MD: 1.01 days; 95% CI 0.47-1.56 days; p < 0.001) in the drain group. The use of prophylactic drainage showed no beneficial effects after major liver resection; however, the definitions and classifications used to report on postoperative complications and surgical complexity are heterogeneous among the published studies. Further well-designed RCTs with large sample sizes are required to conclusively determine the effects of drainage after major liver resection.
Gesehen am 27.05.2021